2009
DOI: 10.1521/aeap.2009.21.6.570
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Voluntary HIV Counseling and Testing among Rural Migrants in Shanghai, China

Abstract: A study of knowledge, attitudes and practices (KAP) of voluntary HIV counseling and testing (VCT) among rural migrants was conducted in Shanghai, China. An anonymous questionnaire was administered face-to-face. Among 2,690 participants, 78% reported having had lifetime sexual intercourse with 41.3% of singles reporting sexual intercourse, 9.2% having had multiple sex partners in the past year, only 19% of the participants always using condoms whereas 61.6% did not use in their sexual acts in the past month, 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
3
38
1
1
Order By: Relevance
“…Despite its controversies, the new polices have led to higher rates of HIV testing, especially in at-risk populations [17]. HIV testing in general populations, including migrant workers and market vendors remained very low (2.3-6%) [18][19][20]. Similar to those reported in international literature, HIV testing in the general population was associated with older age, higher level of education, and perceived higher risks of HIV infection [8,21].…”
Section: Introductionmentioning
confidence: 70%
“…Despite its controversies, the new polices have led to higher rates of HIV testing, especially in at-risk populations [17]. HIV testing in general populations, including migrant workers and market vendors remained very low (2.3-6%) [18][19][20]. Similar to those reported in international literature, HIV testing in the general population was associated with older age, higher level of education, and perceived higher risks of HIV infection [8,21].…”
Section: Introductionmentioning
confidence: 70%
“…7,8,20,21,28 FSW-specific studies have also found that some FSWs avoid testing because of fear that VCT utilization will publicize the nature of their work. 10 Perhaps in part because of these types of stigma, FSWs from other parts of or outside of Yunnan were more likely to follow-up in comparison to those from Gejiu and Kaiyuan, who might face higher risks of being “outted” in closer proximity to their hometowns.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, over half of those living with HIV do not know their serostatus 1 and low levels of HIV test uptake have been noted among many Chinese with increased sexual risk. 2 In response to the need to scale up routine HIV testing in China, the government established free HIV VCT testing sites and piloted HIV provider-initiated testing and counseling (PITC). 3 But VCT sites have not been successful in expanding HIV test uptake, averaging two tests per day per site.…”
Section: Introductionmentioning
confidence: 99%